Figure of Eight Stereotypies in a Young Girl With a Prenatal Cerebellar Injury. Issue 6 (11th May 2019) - Dean, Shannon L.; Huisman, Thierry A.G.M.; Poretti, Andrea; Singer, Harvey S.
Abstract : View Supplementary Video 1